(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2018)
The article focuses on the idea of participation in contemporary art practice, analyzed through Carsten Höller’s artistic production. Starting from Guy Debord’s essay La société du spectacle, the public is no longer seen as an alienated mass of spectators, but it begins to participate by taking part in the activation of artworks, as pointed out in Nicolas Bourriad’s Esthétique Relationnelle. Like a scientist, Höller examines the viewer as if it was a lab rat, similar to the ones of Mäuserplatz black and Mäuserplatz white. The observation of the interaction between the public and Höller’s works shows that it is not only the idea of fruition to be redefined, but the whole concept of aesthetic experience.